Does corporate governance influence firm performance? Evidence from India - Saha Rupjyoti; Kabra Kailash Chandra (Economics and Business Review, 2019)
Corporate Governance (CG) in India has undergone major transformation in the recent past with the enactment of Companies Act, 2013 and revision of SEBI’s Listing Agreement. Though some studies were undertaken in the Indian context few conventional aspects of CG have been repetitively addressed with conflicting results. The aim of this study is to examine the impact of some prominent CG attributes such as board size, board independence, role duality, board’s gender diversity, ownership concentration and audit committee independence on both market as well as accounting based measures of firm performance (FP). To this end the study uses a sample of top 100 non-financial and non-utility firms listed on the Bombay Stock Exchange (BSE) for the period of 2014-2018 and employs two stage least square with instrumental variables technique of estimation which takes into account potential endogeneity in CG-FP relationship. The findings reveal a significant positive impact of board size, ownership concentration and audit committee independence on market based measure of FP while board independence is found to have a significant negative impact on accounting based measure of FP. Moreover role duality and gender diversity are not associated with FP. The outcome of this study highlights how the relationship between CG and FP works in the unique institutional setting of India and it should be of interest to regulators, practitioners and other market participants.